Basics. - Fibicher, Bernhard; Kunsthalle Bern, Bern (Bern : Kunsthalle, 2002)
Bismuth, Pierre ; Courbot, Didier ; Creed, Martin ; Dolven, Anne Katrine ; Epars, Ariane ; Grcic, Tamara ; Hassan, Kay ; Hirschhorn, Thomas ; Huws, Bethan ; Lischetti, Carlo E. ; Löhr, Christiane ; Monk, Jonathan ; Cabrita Reis, Pedro ; Rütimann, Christoph ; Semper, Jonty ; Seric-Soba, Nebojsa ; Shrigley, David ; Signer, Roman ; Solakov, Nedko ; Takahashi, Tomoko ; Tasset, Tony ; Terfloth, Beate ; Verjux, Michel ; Zaugg, Rémy ; Ziegler, Mel
biog. p. 99
Duits
Engels
Basics, Kunsthalle Bern, 23.3. - 28.4.2002
kunstcatalogus